PENGARUH TERAPI BERCERITA MENGGUNAKAN BONEKA TANGAN TERHADAP NYERI SAAT PEMASANGAN INFUS PADA USIA PRA SEKOLAH - Rillia " Handayani; Riri " Novayelinda; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractIntravenous infusion is an invasive treatment that can cause pain for children. One of easy non pharmacology technic can be done by nurse and theoretically effective to reduce pain when invasive treatment for children is playing a story telling technic. The objective of this research is to know the effect playing a story telling use hand puppet toward reducing pain when intravenous infusion on preschool children. Data collection was done from December 2016 – January 2017 at Dumai public hospital, using quasi experiment design with posttest only nonequivalent control group approach. Sampling technic used is purposive sampling with numbers of sample as many as 36 children of preschool age (3-5 years old), 18 kids were experiment group and 18 kids were control group. Pain when infusions to the kids measured directly with FLACC scale (Face, Legs, Activity, Cry, Consolability). Data analysis was done by t test independent to asses average different significant pain scale (p<0, 05) between kids which were given hand puppet story telling therapy and the kids which weren’t given  hand puppet story telling therapy when intravenous infusion. This is recommended for nurse and other healthcare provider to use story telling therapy as non-pharmacology technic when intravenous infusion in order to make lower pain scale for children. Key words : intravenous infusion, pain scale, storytelling therapy.